PENDIDIKAN BAHASA INDONESIA DI JEPANG - Kyoko Funada (LINGUA : JURNAL ILMIAH, 2019)
BIPA is an abbreviation for Indonesian for Foreign Speakers. Precisely, Indonesian language skills learning programs, namely speaking, writing, reading, and listening to foreign speakers. In Japan, Indonesian is taught at universities, language schools and several high schools. In some universities Indonesian language can be learned as a second foreign language / language of choice after they learn English. In general, the material taught is only about language. However, there are several universities that have Indonesian Language Study Programs or Programs. The scope of teaching is broader. In addition to language, those who take the program can study the arts, culture, literature, religion, social, economics, and politics of Indonesia. Can I study Indonesian language in a department or study program that can be called BIPA? According to the author it is different from BIPA because BIPA is only limited to language learning. Indonesian (Malay) education in Japan began in the early 1900s in Tokyo. This article discusses the development of Indonesian language education in Japan from the past to the present.